A personal device for analyzing carbon dioxide in real time and real breath: experimental investigation and computational simulation - Zhao, Di (2013)
The analysis of breath CO2 provides valuable information of pulmonary and cardiovascular functions, and plays a crucial role in monitoring patients with respiratory problems. Developing portable sensors for real breath CO2 analysis has been challenging because exhaled breath is hot, humid and turbulent. In this work, we have developed, modeled and tested a portable CO2 sensor that can analyze end tidal CO2 concentration in breath and in real time accurately. The key components of the sensor comprise a fluidic system for efficient breath sample delivery and a colorimetric detection integrated into the fluidic system. The modeling includes turbulent mass transport, heat transfer from the samples at body temperature to the device environment, and chemical reaction mechanisms, including multiple reactions pathways and diffusion of CO2 in the sensing layer. Furthermore, the sensor has been tested and compared with a standard commercial CO2 analyzer, and the results are in good agreement with those of the commercial analyzer, and with the modeling.